Work‐life support practices and customer satisfaction: The role of TMT composition and country culture - Cogin, Julie A.; Sanders, Karin; Williamson, Ian O. (Human Resource Management, 2018)
Despite the growing prevalence of work‐life support (WLS) practices in companies, there is a lack of theoretical and empirical clarity on their benefits to organizational performance. It is also unclear if the organizational performance effects of WLS practices vary based on an organization's internal and external environments. The dual objective of this paper is to investigate whether WLS practices relate to customer‐focused outcomes and, if so, under which conditions WLS practices yield benefits. Drawing on contingency theory, we examine how the boundary conditions of internal firm characteristics (e.g., percentage of top management team [TMT] members with children) and external environmental factors (e.g., gender egalitarianism of the country) moderate the relationship between WLS practices and customer satisfaction. We shed light on these issues by examining multisource, longitudinal data collected over three years from a multinational corporation operating in 27 countries. The results show that both percentage of TMT members with children and gender egalitarianism of the country strengthen the relationship between WLS practices and customer satisfaction. The findings provide insights into the circumstances when WLS practices provide performance benefits for firms and the translatability of these benefits from one country to another.